Social capital as an interdisciplinary concept - Libertowska, Andżelika (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The main purpose of the article was to present the interdisciplinary nature of the concept of social capital on the basis of own research. Methodology: The research method used was a scientometric analysis conducted based on items found in the Web of Science database. For the literature search visualisation was performed using the VOSviewer application, and the methodology used allowed for a comprehensive assessment of the co-occurrence of keywords in scientific publications on social capital, as well as an overview of the scientific categories to which these publications were assigned. Results: The analyses led to conclude that the concept of social capital is correlated with a wide range of terms anchored in various research disciplines. The perceived multiplicity of approaches to the category of social capital in the literature also results in the wealth of scientific definitions formulated and the possibilities of operationalisation, which further strengthens the interdisciplinary evaluation of this category. This is evident in attempts to embed it on various cognitive levels and to assign multiple causal powers based on the considerations carried out. Implications and recommendations: This article attempts to fill the cognitive gap in the analysis of the interdisciplinary nature of the concept of social capital. It is an expression of the position taken by the author that the conceptualisation and operationalisation of this category visible in the literature, does not have to be accidental and occasional. The adopted research methodology, i.e. a scientometric analysis, allowed for the elimination of incidental (singular) connections between words of terms co-occurring in the base. Originality/value: The observed multiplicity of definitions of this concept, according to some researchers, indicates its scientific immaturity. However, there is still a belief in the many positive effects that the building of social capital and its proper use in various social groups causes. In the author’s opinion the conducted research is scientifically justified as it provides a clear statement about the interdisciplinary nature of the category of social capital. Keywords: social capital, interdisciplinarity, trust, scientometric analysis, keyword map
Argumenta Oeconomica, 2025, Nr 2 (55), s. 52-63
Keywords: social capital; interdisciplinarity; trust; scientometric analysis; keyword map